Lectures on classical mechanics - Englert, Berthold-georg; Englert, Berthold-georg (Singapore, World Scientific Publishing, 2015)
These lecture notes cover Classical Mechanics at the level of secondyear undergraduates. The book offers comprehensive as well as selfcontained material that can be taught in a onesemester course for students with the minimal background knowledge acquired in preuniversity education or in the usual firstyear overview. The presentation does not skip the technical details which renders the book particularly wellsuited for the selfstudying student.
Index 339-353p.; Appendix A-C 323-338p.
Keywords: Conservation forces; Pair forces; Variational problems; Rigid bodies